(untitled) (ARQUISUR Revista, 2011)
This work emerges from a reflection based on the research carried out for the Doctoral Thesis: «Theory and Practice of the Architectural Project» which addresses the capacity of the cinematographic resource in architecture teaching. The proposal consists in alternative exercises different from the traditional ones, specially designed for architecture students. The exercises handle the potential value of the cinema as a tool for developing our perception and reflection, thus stimulating the rational and emotional aspects of each person. It is based on the comparative method which allows the establishment of relations among different realities: between fiction and reality and between different fiction worlds. It has been structured into three modules of increasing difficulty. Each one initiates its discourse with a hypothesis formulation which must be demonstrated and triggers a research process where the student’s knowledge, reasoning and ability to evaluate are put into play through a set of exercises. These involve the graphic survey of film spaces, cinematic languages and significance perception systems in order to detect archetypical architectural spaces common to different films. In this particular case, the proposal is addressed to the analysis of interior domestic spaces and its furnishings.